Synaptic adhesion molecules in Cadm family at the neuromuscular junction. (18th April 2013) - Tanabe, Yuko; Fujita, Eriko; Hayashi, Yukiko K.; Zhu, Xinran; Lubbert, Hermann; Mezaki, Yoshihiro; Senoo, Haruki; Momoi, Takashi
Abstract RA175/SynCAM1/Cadm1 (Cadm1), a member of the immunoglobulin superfamily, is a synaptic cell adhesion molecule that has a PDZ‐binding motif at the C‐terminal region. It promotes the formation of presynaptic terminals and induces functional synapses in the central nervous system. Cadm1‐deficient (knockout [KO]) mice show behavioral abnormalities, including excessive aggression and anxiety, but do not show any symptoms of neuromuscular disorder, although neuromuscular junctions (NMJs) have structures similar to synapses. We have examined the expression of members of the Cadm family in the mouse muscle tissues. Cadm4 and Cadm1 were major components of the Cadm family, and Cadm3 was faintly detected, but Cadm2 was not detected by RT‐PCR. Cadm4 as well as Cadm1 colocalized with alpha‐bungarotoxin at the NMJs and interacted with the multiple PDZ domain protein Mupp1. Cadm4 was expressed in Cadm1‐KO mice and might compensate for Cadm1 loss through interactions with Mupp1.